Caracteristicas Microbianas y fermentativas del ensilaje de pasto saboya (Panicum maximun) asociados con diferentes niveles de inclusion de cascaras de maracuya (Passiflora edulis). - Hurtado Mecias, Jessica Margarita (2015)
In order to assess the microbiological and fermentation characteristics of silage grass Savoy containing residue levels of passion fruit peel (RCM). 10, 20, 30 and 40% over the grass Savoie The values in the variables were analyzed as a complete randomized design, the Tukey test was used to compare means low probability levels of P <0.05. The process of the silage was made in laboratory facilities Rumiología and Nutritional Metabolism in microsilos made with PVC tubes with a length of 30 to 10 cm in diameter, with a storage capacity of 3 kg. 60 microsilos laboratory, corresponding to 4 treatments 3 and 5 replicates fermentation periods (14, 21 and 28 days) was used. The growth of lactic acid bacteria (BAL) showed no significant difference (P 0.05) at 14 and 28 days of fermentation, whereas at 21 days showed differences (P 0.05) with T3 T2, while T1, T2 and T4 obtained similar behavior (p 0.05). For total bacterial count (BT) there was no significant difference (p> 0.05) at 14 and 28 days between treatments, at 21 days showed significant differences (p <0.05) between treatments T2. For the growth of fungi, there were significant differences (p <0.05) at 14 days of opening the silos, at 21 and 28 days showed no significant difference (p> 0.05) between treatments. No significant difference was found (P 0.05) for yeast growth in the openings of the microsilos at 14, 21 and 28 days. The temperature values (° C) at the opening at 14, 21 and 28 days there was no difference (p> 0.05) at 24, 48, 72, 96, 120 and 144 hours of exposure were different (P 0.05 ) at 0 hours compared to T3 T1 at 14 days, 21 days only when 0 T2, T3 and T4 were different (p <0.05) with T1. significant difference (p She found <0.05) for variable pH at 0, 24 and 120 hours, while at 48, 72, 96 and 144 hours showed no differences (p> 0.05) between treatments, so there was no influence agricultural waste in relation to T1, T3 and T4, at 28 days of opening microsilos significant differences (p <0.05) was found at times 0, 24, 96 and 144 hours, the T4 significantly different ( p 0.05) between treatments for this variable pH <0.05) with the other treatments at 0 hours, at times 48, 72, 120 and 144 hours no significant differences (p was found>, so that there was no influence of agricultural waste. Keywords: Bacteria, yeast, fungi, pH, temperature